Targeted Neonatal Echocardiography-Guided Therapy in Vein of Galen Aneurysmal Malformation: A Report of Two Cases with a Review of Physiology and Approach to Management - R. E. Giesinger; Y. N. Elsayed; M. P. Castaldo; P. J. McNamara (Thieme Medical Publishers, Inc., 2019)
Vein of Galen malformation results in predictable changes in physiology which exist on a continuum. Severe pulmonary hypertension may present as hypoxemia; however, excessive reduction in pulmonary vascular resistance may precipitate progressive pulmonary overcirculation and impaired systemic blood flow. Right ventricular performance and the patency and direction of the ductus arteriosus may play a crucial role in postductal organ perfusion. Physiological stabilization may be complex and variable over time. The utilization of targeted neonatal echocardiography to guide treatment decisions may improve the ability to provide therapy tailored to the specific disease pathophysiology and monitor serially as conditions change. An enhanced approach to physiological stabilization may reduce the risk of unexpected decompensation and allow for thoughtful, controlled endovascular embolization in appropriate candidates.